ACTIVE SURVEILLANCE BASED RANKING ORDER AND TEMPORAL DISTRIBUTION OF PARTURIENT HAEMOGLOBINURIA CASES IN BUFFALO POPULATION IN DISTRICT CHAKWAL, PAKISTAN (Pakistan Journal of Science, 2015)
A descriptive epidemiological study was carried out for understanding the ranking order and temporal distribution of parturient haemoglobinuria in buffalo. For this data was recorded from each household of eight randomly selected villages. Parturient haemoglobinuria ranked as number one disease among all observed cases with respect to mortality (1.03%) and proportional mortality (29.41%) rate and appeared as 4thand 3rdposition in ranking with respect to incidence (3.97%) and case fatality (25.97%) rate. For assessment of temporal distribution, data of 77 haemoglobinuria cases was analyzed. Significantly (P
Keywords: Parturient haemoglobinuria; epidemiological studyranking order; active surveillance; buffalo